Efektivitas Daylight Mirror Shaft sebagai Sistem Pencahayaan Alami Ruang Bawah Tanah pada Langit Tropis - Seline Adella Margono; Mira Dewi Pangestu (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2021)
Title: Effectiveness of Daylight Mirror Shafts as Natural Daylighting System for Basements under Tropic Sky Conditions Basements have lots of potential as functional spaces, but have mostly been neglected due to lighting issues. Therefore, this study will explore the daylight mirror shaft system as a daylight strategy for basements, which features the placement of a reflecting surface on a light shaft to redirect daylight. The system was introduced by Heliobus®, a daylighting company from Switzerland. To see the effectiveness of implementing the system in Indonesia, a study was made on its performance on the climate sky condition. Furthermore, a study was made on the effect of different opening orientations and light shaft placements toward the illuminance level achieved. The lighting data was obtained using the simulation softwares Lightstanza. Results show that the performance of the system on climate sky condition can provide sufficient light for 41% of a basement. The use of mirrors on the light shaft could also increase the lighting levels by 2.1 times compared to a shaft without a mirror. Moreover, it was found that different opening orientations and light shaft placements didn’t give a significant effect on the lighting quantity. Overall, the study shows that the system’s implementation on climate skies still require adjustments through further studies to be effective.